Association between SARS-CoV-2 infection and self-harm: Danish nationwide register-based cohort study. (April 2023) - Erlangsen, Annette; Qin, Ping; Madsen, Trine; Hawton, Keith; Osler, Merete; Hjorthøj, Carsten; Benros, Michael E.; Ethelberg, Steen; Mølbak, Kåre; Laursen, Thomas Munk; Nordentoft, Merete; Nilsson, Sandra Feodor
Abstract : Background: Case studies have linked SARS-CoV-2 infection to suicidal behaviour. However, conclusive evidence is lacking. Aims: To examine whether a history of SARS-CoV-2 infection or SARS-CoV-2-related hospital admission was associated with self-harm in the general population and in high-risk groups. Method: A cohort design was applied to nationwide data on all people aged ≥15 years and living in Denmark between 27 February 2020 and 15 October 2021. Exposure was identified as having had a positive SARS-CoV-2 PCR test, and further assessed as SARS-CoV-2-related hospital admission. Rates of probable self-harm were examined using adjusted incidence rate ratios (aIRRs). The following subgroups were identified: (a) lower educational level, (b) chronic medical conditions, (c) disability pension, (d) mental disorders, (e) substance use disorders, and history of (f) homelessness and (g) imprisonment. Results: Among 4 412 248 included individuals, 260 663 (5.9%) had tested positive for SARS-CoV-2. Out of 5453 individuals presenting with self-harm, 131 (2.4%) had been infected. Individuals with a history of a positive SARS-CoV-2 test result had an aIRR for self-harm of 0.86 (95% CI 0.72–1.03) compared with those without. High rates were found after a SARS-CoV-2-related hospital admission (aIRR = 7.68; 95% CI 5.61–10.51) or a non-SARS-CoV-2-related admission (aIRR = 10.27; 95% CI 9.65–10.93) versus non-infected and not admitted. In sensitivity analyses with a more restrictive definition of self-harm, a positive PCR test was associated with lower rates of self-harm. Conclusions: Individuals with a PCR-confirmed SARS-CoV-2 infection did not have higher rates of self-harm than those without. Hospital admission in general, rather than being SARS-CoV-2 positive. seemed to be linked to elevated rates of self-harm.